Forecasting Sales of Hex Nut Using Trend Linier Line (TLL) Methode and Monte Carlo Simulation in PT. KMS East Java - Apriliana Sari W., Indah; Isma P., Boy; Nurdiansyah, Rudi (UNIPA PRESS, 2022)
This study presenting the result of forecasting sales of Hex Nuts between the Trend Linear Line (TLL) method and Monte Carlo Simulation. To determine the appropriate method, the Mean Average Percentage Error (MAPE) is used to evaluate theerror rate. We find that the Monte Carlo simulation outperforms the TTL method, where the MAPE value of the Monte Carlo simulation is 7,61%. Based on the result, the Monte Carlo simulation is the appropriate method to forecast the sales rate of Hex Nuts in the PT. KMS.